1991
DOI: 10.1210/endo-129-6-2834
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Distribution of Aromatase Cytochrome P450 in the Rat Brain Using Peptide-Generated Polyclonal Antibodies*

Abstract: Estrogen formation is catalyzed by the aromatase cytochrome P450 (P450AROM) enzyme. Aromatase activity has been detected in several regions in the rat brain. In the present study, we used peptide-generated polyclonal antibodies raised against a 20-amino acid synthetic fragment of the rat P450AROM protein (as deduced from the nucleic acid sequence of the rat P450AROM complementary DNA), to determine the location of this enzyme in rat brain sections. Immunoreactive antisera were titered by means of an enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(73 citation statements)
references
References 38 publications
7
66
0
Order By: Relevance
“…Testosterone could be converted to estrogen and then act through the estrogen receptors (ER). The immunocytochemical distribution of c-Fos expression found in the brain of testosteronetreated, fasted castrates is consistent with that of aromatase activity or immunoreactivity [34][35][36], or ER mRNA [37] previously reported. Increased expression of ER mRNA has been shown in the PVN, SON, AMYG and NTS [37] where FLI was also found after 6-h fasting in testosterone-treated castrates in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Testosterone could be converted to estrogen and then act through the estrogen receptors (ER). The immunocytochemical distribution of c-Fos expression found in the brain of testosteronetreated, fasted castrates is consistent with that of aromatase activity or immunoreactivity [34][35][36], or ER mRNA [37] previously reported. Increased expression of ER mRNA has been shown in the PVN, SON, AMYG and NTS [37] where FLI was also found after 6-h fasting in testosterone-treated castrates in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Results from several laboratories over the past decade have established unequivocally that the enzymes found in classic steroidogenic tissues are present in the CNS (Compagnone and Mellon, 2000). Aromatase, which transforms testosterone to estradiol, has been detected in rat hippocampal neurons both at the mRNA level (Abdelgadir et al, 1994;Wehrenberg et al, 2001) and protein level (Sanghera et al, 1991;Garcia-Segura et al, 1999, 2001). Recently, it was shown that adult hippocampal neurons indeed synthesize estrogens (Prange-Kiel et al, 2003).…”
Section: Letrozole As a Tool To Study Estrogen Effects In Neural Tissuementioning
confidence: 99%
“…Since it appears that aromatase is present in or near the PVN (Lund et al 2006, Sanghera et al, 1991 this presents a potential interpretive problem for the HPA of both males (as a result of testosterone aromatization to estradiol) and females. One possibility lies in the ratio of ERalpha to ERbeta that exists within neurons in and around of the PVN.…”
Section: -β-Diol Regulation Of the Hpa Axismentioning
confidence: 99%